Study of Kumaon Language for Natural Language Processing in End-to-End Conversation Scenario - Rawat, Bhupesh; Bist, Ankur Singh; Mehra, Nidhi; Fazri, Muhammad Faizal; Terah, Yochebed Anggraini (Pandawan Sejahtera Indonesia, 2022)
Natural language processing is one of the essential activities of artificial intelligence. There is an excellent need for chatbots that require integration into artificial intelligence applications. The local language makes the process easier. Our research aims to analyze the possibilities and challenges of implementing a chatbot in the Kumaon language. We also provide a detailed survey of the Kumaon language and map it to other languages to make it easier to process it for industrial use. This chatbot can help with various needs and services in the Kumaon language. The method used in this research is a study analysis of the Kumaon language to deal with language extinction. The novelty in this research is a chatbot in the Kumaon language with end-to-end encryption so that the service user has good security.